Gaugamela in the Plains of Nineveh? The Southern Location of the Battle of Gaugamela Reconsidered - Marciak, Michał; Głogowski, Piotr; Szypuła, Bartłomiej; Pirowski, Tomasz; Gomiero, Giovanni (Anabasis. Studia Classica et Orientalia, 2020)
This paper is devoted to a critical interdisciplinary reassessment of the recently revived localization of the Battle of Gaugamela at the Plateau of Karamleis. Several conclusions are suggested. First, on the basis of literary sources, it is only possible to suggest a general geographical context of the battle. In particular, compliance with the distances mentioned in the sources cannot be seen as a solution to the identification of Gaugamela. Second, the connection between Gaugamela and Nineveh in later incidental literary references has a genuine geographical background – Gaugamela was part of the region of Nineveh. However, this region did not include only the immediate vicinity of Nineveh, but also its wider hinterland. Third, out of many geographical details in ancient sources, the reference to the Bumelus/Bumodus River is more useful than others. Although this river may theoretically be identified with both the Gomel and the Shore Dereh rivers, the former identification has stronger paleographical and topographical merits. As for previous topographical research, the identification of Gaugamela with the Plateau of Karamleis was formulated much earlier than its northern alternative at Tell Gomel. However, this identification was deeply conditioned by the limited regional perspective of the earliest explorers - Karamleis was located on the axis of the contemporary travel between Mosul and Baghdad, it also attracted the attention of European scholars because of Assyrian cities and itinerary of the Ten Thousand in 401 BCE. Finally, through the use of GIS and satellite archaeology, this identification has been shown to lack three important elements: visibility on the battlefield, a distinctive accumulation of sloped areas, and post-battle remains. All in all, in the current state of research, the identification of the Battle of Gaugamela at the Plateau of Karamleis is significantly surpassed by its northern alternative at Tell Gomel.